K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

16 tháng 1 2018

Ta có:

Chọn D.

10 tháng 11 2023

a: \(\lim\limits_{x\rightarrow3}\dfrac{\sqrt{2x+10}-4}{3x-9}\)

\(=\lim\limits_{x\rightarrow3}\dfrac{2x+10-16}{3x-9}\cdot\dfrac{1}{\sqrt{2x+10}+4}\)

\(=\lim\limits_{x\rightarrow3}\dfrac{2\left(x-3\right)}{3\left(x-3\right)\cdot\left(\sqrt{2x+10}+4\right)}\)

\(=\lim\limits_{x\rightarrow3}\dfrac{2}{3\left(\sqrt{2x+10}+4\right)}\)

\(=\dfrac{2}{3\cdot\sqrt{6+10}+3\cdot4}=\dfrac{2}{3\cdot4+3\cdot4}=\dfrac{2}{24}=\dfrac{1}{12}\)

b: \(\lim\limits_{x\rightarrow7}\dfrac{\sqrt{4x+8}-6}{x^2-9x+14}\)

\(=\lim\limits_{x\rightarrow7}\dfrac{4x+8-36}{\sqrt{4x+8}+6}\cdot\dfrac{1}{\left(x-2\right)\left(x-7\right)}\)

\(=\lim\limits_{x\rightarrow7}\dfrac{4x-28}{\left(\sqrt{4x+8}+6\right)\cdot\left(x-2\right)\left(x-7\right)}\)

\(=\lim\limits_{x\rightarrow7}\dfrac{4}{\left(\sqrt{4x+8}+6\right)\left(x-2\right)}\)

\(=\dfrac{4}{\left(\sqrt{4\cdot7+8}+6\right)\left(7-2\right)}\)

\(=\dfrac{4}{5\cdot12}=\dfrac{4}{60}=\dfrac{1}{15}\)

c: \(\lim\limits_{x\rightarrow5}\dfrac{x^2-8x+15}{2x^2-9x-5}\)

\(=\lim\limits_{x\rightarrow5}\dfrac{\left(x-3\right)\left(x-5\right)}{2x^2-10x+x-5}\)

\(=\lim\limits_{x\rightarrow5}\dfrac{\left(x-3\right)\left(x-5\right)}{\left(x-5\right)\left(2x+1\right)}\)

\(=\lim\limits_{x\rightarrow5}\dfrac{x-3}{2x+1}=\dfrac{5-3}{2\cdot5+1}=\dfrac{2}{11}\)

NV
25 tháng 2 2020

\(a=\lim\limits_{x\rightarrow3}\frac{\left(x-3\right)\left(2x+3\right)}{\left(x-3\right)\left(x^3+3x^2+9x\right)}=\lim\limits_{x\rightarrow3}\frac{2x+3}{x^3+3x^2+9x}=\frac{2.3+3}{3^3+2.3^2+9.3}=...\)

\(b=\lim\limits_{x\rightarrow1}\frac{\left(x-1\right)\left(x+1\right)}{\left(x-1\right)\left(x^4+x^2+2x^3+2x+2\right)}=\frac{1+1}{1+1+2+2+2}=...\)

\(c=\lim\limits_{x\rightarrow1}\frac{\left(x-1\right)^2\left(4x^3+3x^2+2x+1\right)}{\left(x-1\right)^2\left(x^2+x+2\right)}=\frac{4+3+2+1}{1+1+2}=...\)

\(d=\lim\limits_{x\rightarrow-1}\frac{\left(x+1\right)\left(x^4-x^3+x^2-x+1\right)}{\left(x+1\right)\left(x^2-x+1\right)}=\frac{1+1+1+1+1}{1+1+1}=...\)

26 tháng 5 2021

\(Lim_{x\rightarrow3}\frac{x^4-27x}{2x^2-3x-9}=Lim_{x\rightarrow3}\frac{x\left(x^3-3^3\right)}{\left(x-3\right)\left(2x+3\right)}\)

\(=Lim_{x\rightarrow3}\frac{x\left(x-3\right)\left(x^2+3x+9\right)}{\left(x-3\right)\left(2x+3\right)}=Lim_{x\rightarrow3}\frac{x\left(x^2+3x+9\right)}{2x+3}\)

\(=\frac{3\left(3^2+3.3+9\right)}{3.2+3}=\frac{3\left(9+9+9\right)}{9}=9\)

Vậy \(Lim_{x\rightarrow3}\frac{x^4-27x}{2x^2-3x-9}=9\)

1) Ta có: \(\left(\dfrac{3}{4}\cdot\dfrac{5}{97}+\dfrac{1}{9}\cdot\dfrac{13}{47}\right)\cdot\left(\dfrac{1}{5}-\dfrac{7}{25}\cdot\dfrac{5}{7}\right)\)

\(=\left(\dfrac{3}{4}\cdot\dfrac{5}{97}+\dfrac{1}{9}\cdot\dfrac{13}{47}\right)\cdot\left(\dfrac{1}{5}-\dfrac{1}{5}\right)\)

=0

2) Ta có: \(\dfrac{8}{17}\cdot\dfrac{4}{15}+\dfrac{8}{17}\cdot\dfrac{22}{15}-\dfrac{8}{15}\cdot\dfrac{9}{17}\)

\(=\dfrac{8}{17}\left(\dfrac{4}{15}+\dfrac{22}{15}-\dfrac{9}{15}\right)\)

\(=\dfrac{8}{17}\cdot\dfrac{15}{15}=\dfrac{8}{17}\)

3) Ta có: \(\dfrac{2021}{2}\cdot\dfrac{1}{3}+\dfrac{4042}{4}\cdot\dfrac{1}{5}+\dfrac{6063}{3}\cdot\dfrac{22}{15}\)

\(=\dfrac{2021}{2}\left(\dfrac{1}{3}+\dfrac{1}{5}\right)+2021\cdot\dfrac{22}{15}\)

\(=\dfrac{2021}{2}\cdot\dfrac{8}{15}+\dfrac{2021}{2}\cdot\dfrac{44}{15}\)

\(=\dfrac{2021}{2}\cdot\dfrac{52}{15}\)

\(=\dfrac{52546}{15}\)

4) Ta có: \(\dfrac{4}{7}\cdot\dfrac{2}{13}+\dfrac{8}{13}:\dfrac{7}{4}+\dfrac{4}{7}:\dfrac{13}{2}+\dfrac{4}{7}\cdot\dfrac{1}{13}\)

\(=\dfrac{4}{7}\left(\dfrac{2}{13}+\dfrac{8}{13}+\dfrac{2}{13}+\dfrac{1}{13}\right)\)

\(=\dfrac{4}{7}\)

2 tháng 7 2021

cảm ơn nhé

vui

20 tháng 4 2017

a,Cách 1:     (6/11 + 5/11 ) x 3/7                                             Cách 2 :(6/11 + 5/11) x 3/7

                 =       1     x 3/7                                                              =6/11 x 3/7  + 5/11 x 3/7

                  =            3/7                                                                  =      18/77   +     15/77 

                                                                                                      =                3/7

b, Cách 1:3/5 x 7/9 -  3/5 x 2/9                                               Cách 2 :3/5 x 7/9 - 3/5 x 2/9

            =    7/15    -       2/15                                                           = 3/5 x (7/9 - 2/9 )    

            =             1/3                                                                      = 3/5  x     5/9

                                                                                                      =       1/3

c, Cách 1:(6/7 - 4/7) : 2/5                                                      Cách 2: ( 6/7- 4/7 ) : 2/5 

             =     2/7     :  2/5                                                                =     6/7 : 2/5 - 4/7 : 2/5

            =         5/7                                                                         =       15/7    -       10/7  

                                                                                                    =                5/7

d,Cách 1:8/15 : 2/11 + 7/15 : 2/11                                         Cách 2:8/15 : 2/11 +7/15 : 2/11

            =  88/30       +     77/30                                                      =(8/15+7/15) :2/11

            =            11/2                                                                    =   1   :      2/11

                                                                                                    =        11/2

Bài 2 cậu tự làm nhé !                                                             

22 tháng 4 2017

\(2a.160\)

\(b.2\)

\(c.\frac{8064}{5}\)

\(d.\frac{1}{3}\)

a: \(\dfrac{-8}{3}\cdot\dfrac{15}{24}=\dfrac{-8}{24}\cdot\dfrac{15}{3}=\dfrac{-1}{3}\cdot5=-\dfrac{5}{3}\)

b: \(=\dfrac{3}{4}\cdot\dfrac{1}{-9}=\dfrac{-1}{12}\)

c: \(x=-\dfrac{7}{6}+\dfrac{5}{8}=-\dfrac{13}{24}\)

d: \(x=-\dfrac{14}{25}-\dfrac{3}{4}=\dfrac{-56-75}{100}=\dfrac{-131}{100}\)

NV
5 tháng 3 2022

\(\lim\limits_{x\rightarrow0}\dfrac{\sqrt{x^2+1}-\left(x+1\right)}{2x^2-x}=\lim\limits_{x\rightarrow0}\dfrac{\left(\sqrt{x^2+1}-\left(x+1\right)\right)\left(\sqrt{x^2+1}+x+1\right)}{x\left(2x-1\right)\left(\sqrt{x^2+1}+x+1\right)}\)

\(=\lim\limits_{x\rightarrow0}\dfrac{-2x}{x\left(2x-1\right)\left(\sqrt{x^2+1}+x+1\right)}\)

\(=\lim\limits_{x\rightarrow0}\dfrac{-2}{\left(2x-1\right)\left(\sqrt{x^2+1}+x+1\right)}\)

\(=\dfrac{-2}{\left(0-1\right)\left(\sqrt{1}+1\right)}=1\)

a. \(\lim\limits_{x\rightarrow2}\dfrac{x-2}{x^2-4}=\lim\limits_{x\rightarrow2}\dfrac{x-2}{\left(x-2\right)\left(x+2\right)}=\lim\limits_{x\rightarrow2}\dfrac{1}{x+2}=\dfrac{1}{4}\)

b. \(\lim\limits_{x\rightarrow3^-}\dfrac{x+3}{x-3}=\lim\limits_{x\rightarrow3^-}\dfrac{-x-3}{3-x}\)

Do \(\lim\limits_{x\rightarrow3^-}\left(-x-3\right)=-6< 0\)

\(\lim\limits_{x\rightarrow3^-}\left(3-x\right)=0\) và \(3-x>0;\forall x< 3\)

\(\Rightarrow\lim\limits_{x\rightarrow3^-}\dfrac{-x-3}{3-x}=-\infty\)

2 tháng 3 2019

\(a.60\times\left(\frac{7}{12}+\frac{4}{15}\right)\)

\(=60\times\left(\frac{35}{60}+\frac{16}{60}\right)\)

\(=60\times\frac{51}{60}\)

\(=51\)

\(b.\frac{1}{2}\times\frac{2}{3}\times\frac{3}{4}\times\frac{4}{5}\times\frac{5}{6}\times\frac{6}{7}\times\frac{7}{8}\times\frac{8}{9}\)

\(=\frac{1\times2\times3\times4\times5\times6\times7\times8}{2\times3\times4\times5\times6\times7\times8\times9}\)

\(=\frac{1}{9}\)

8 tháng 2 2023

`5`

`a, -7/21 +(1+1/3)`

`=-7/21 + ( 3/3 + 1/3)`

`=-7/21+ 4/3`

`=-7/21+ 28/21`

`= 21/21`

`=1`

`b, 2/15 + ( 5/9 + (-6)/9)`

`= 2/15 + (-1/9)`

`= 1/45`

`c, (9-1/5+3/12) +(-3/4)`

`= ( 45/5-1/5 + 3/12)+(-3/4)`

`= ( 44/5 + 3/12)+(-3/4)`

`= 9,05 +(-0,75)`

`=8,3`

`6`

`x+7/8 =13/12`

`=>x= 13/12 -7/8`

`=>x=5/24`

`-------`

`-(-6)/12 -x=9/48`

`=> 6/12 -x=9/48`

`=>x= 6/12-9/48`

`=>x=5/16`

`---------`

`x+4/6 =5/25 -(-7)/15`

`=>x+4/6 =1/5 + 7/15`

`=> x+ 4/6=10/15`

`=>x=10/15 -4/6`

`=>x=0`

`----------`

`x+4/5 = 6/20 -(-7)/3`

`=>x+4/5 = 6/20 +7/3`

`=>x+4/5 = 79/30`

`=>x=79/30 -4/5`

`=>x= 79/30-24/30`

`=>x= 55/30`

`=>x= 11/6`

8 tháng 2 2023

\(5)\)

\(A=\dfrac{-7}{21}+\left(1+\dfrac{1}{3}\right)\)

\(A=\dfrac{-7}{21}+\dfrac{4}{3}\)

\(A=\dfrac{-7}{21}+\dfrac{28}{21}\)

\(A=1\)

\(--------------\)

\(B=\dfrac{2}{15}+\left(\dfrac{5}{9}+\dfrac{-6}{9}\right)\)

\(B=\dfrac{2}{15}+\dfrac{-1}{9}\)

\(B=\dfrac{18}{135}+\dfrac{-15}{135}\)

\(B=\dfrac{1}{45}\)

\(------------\)

\(C=9-\dfrac{1}{5}+\dfrac{3}{12}+\dfrac{-3}{4}\)

\(C=\dfrac{44}{5}+\dfrac{3}{12}+\dfrac{-3}{4}\)

\(C=\dfrac{528}{60}+\dfrac{15}{60}+\dfrac{-3}{4}\)

\(C=\dfrac{181}{20}+\dfrac{-3}{4}\)

\(C=\dfrac{181}{20}+\dfrac{-15}{20}\)

\(C=\dfrac{83}{10}\)

\(6)\)

\(a)\) \(x+\dfrac{7}{8}=\dfrac{13}{12}\)

\(x=\dfrac{13}{12}-\dfrac{7}{8}\)

\(x=\dfrac{104}{96}-\dfrac{84}{96}\)

\(x=\dfrac{5}{24}\)

\(b)\) \(\dfrac{-6}{12}-x=\dfrac{9}{48}\)

\(\dfrac{-1}{2}-x=\dfrac{3}{16}\)

\(x=\dfrac{-1}{2}-\dfrac{3}{16}\)

\(x=\dfrac{-8}{16}-\dfrac{3}{16}\)

\(x=\dfrac{-11}{16}\)

\(c)\) \(x+\dfrac{4}{6}=\dfrac{5}{25}-\left(-\dfrac{7}{15}\right)\)

\(x+\dfrac{4}{6}=\dfrac{5}{25}+\dfrac{7}{15}\)

\(x+\dfrac{4}{6}=\dfrac{75}{375}+\dfrac{105}{375}\)

\(x+\dfrac{4}{6}=\dfrac{12}{25}\)

\(x=\dfrac{12}{25}-\dfrac{4}{6}\)

\(x=\dfrac{72}{150}-\dfrac{100}{150}\)

\(x=\dfrac{-14}{75}\)

\(d)\) \(x+\dfrac{4}{5}=\dfrac{6}{20}-\left(-\dfrac{7}{3}\right)\)

\(x+\dfrac{4}{5}=\dfrac{6}{20}+\dfrac{7}{3}\)

\(x+\dfrac{4}{5}=\dfrac{18}{60}+\dfrac{140}{60}\)

\(x+\dfrac{4}{5}=\dfrac{79}{30}\)

\(x=\dfrac{79}{30}-\dfrac{4}{5}\)

\(x=\dfrac{79}{30}-\dfrac{24}{30}\)

\(x=\dfrac{11}{6}\)

15 tháng 2 2023

l

 

12 tháng 8 2023

a) 3/8 . x = 9/8 - 1

3/8 . x = 1/8

x = 1/8 : 3/8

x = 1/3

b) 4/5 . x = 7/5 - 1/5

4/5 . x = 6/5

x = 6/5 : 4/5

x = 3/2

c) 12/7 : x + 2/3 = 7/5

12/7 : x = 7/5 - 2/3

12/7 : x = 11/15

x = 12/7 : 11/15

x = 180/77

d) 3.(x + 7) - 15 = 27

3.(x + 7) = 27 + 15

3.(x + 7) = 42

x + 7 = 42 : 3

x + 7 = 14

x = 14 - 7

x = 7

12 tháng 8 2023

a) \(\dfrac{3}{8}x=\dfrac{9}{8}-1\)

\(\Rightarrow\dfrac{3}{8}x=\dfrac{1}{8}\)

\(\Rightarrow x=\dfrac{1}{8}:\dfrac{3}{8}=\dfrac{1}{3}\)

b) \(\dfrac{4}{5}x=\dfrac{7}{5}-\dfrac{1}{5}\)

\(\Rightarrow\dfrac{4}{5}x=\dfrac{6}{5}\)

\(\Rightarrow x=\dfrac{6}{5}:\dfrac{4}{5}=\dfrac{3}{2}\)

c) \(\dfrac{12}{7}:x+\dfrac{2}{3}=\dfrac{7}{5}\)

\(\Rightarrow\dfrac{12}{7}:x=\dfrac{7}{5}-\dfrac{2}{3}\)

\(\Rightarrow\dfrac{12}{7}:x=\dfrac{11}{15}\)

\(\Rightarrow x=\dfrac{12}{7}:\dfrac{11}{15}=\dfrac{180}{77}\)

d) \(3\left(x+7\right)-15=27\)

\(\Leftrightarrow3\left(x+7\right)=42\)

\(\Leftrightarrow x+7=14\Leftrightarrow x=7\)